A prospective evaluation of subgingival irrigation with i-PRF following non-surgical treatment of peri-implantitis - Deterville, Laurie; Lasserre, Jérôme Frédéric; Toma, Selena (Frontiers in Dental Medicine, 2025)
IntroductionPeri-implantitis, an inflammatory condition around dental implants, is challenging to manage with conventional non-surgical treatments alone. Emerging adjunctive therapies like glycine air-polishing and injectable platelet-rich fibrin (i-PRF) show potential to enhance decontamination.AimTo clinically and radiographically evaluate the efficacy of glycine air-polishing and the adjunctive use of injectable platelet rich fibrin (i-PRF) for the non-surgical treatment of slight peri-implantitis.MethodsFor this prospective case series, nine patients (n = 14 implants), with at least one implant with a slight peri-implantitis (radiographic bone loss visible and up to 4 mm) were enrolled. All treated implants received the same treatment: non-surgical mechanical debridement with an air abrasive device (PERIOFLOW®) followed by a subgingival irrigation with an injectable platelet rich fibrin (i-PRF). The following clinical parameters were measured: Plaque Index (PI), Bleeding on Probing (BoP), Suppuration on Probing (SoP), Probing Pocket Depth (PPD), Relative Attachment Level (RAL) and Recession (REC). They were assessed at baseline (M0), 3 and 6 months (M3 and M6). To compare bone level (BL), radiographs were taken at M0 and M6 (p > 0.05, ANOVA, Bonferroni).ResultsResults indicated that PI significantly decreased over 6 months to a mean value of <0.05. Both BoP (p < 0.05) and SoP (p < 0.05) were substantially reduced at 3 months, although a slight increase was noted at 6 months. Mean PPD was 3.61 ± 0.25 mm (p < 0.05) at M6, and RAL gain was significantly improved at 6 months (7.76 ± 0.34 mm, p < 0.05). BL showed a significant grain at 6 months (p < 0.05). Most mucosal recession occurred within the first 3 months, with no significant change at 6 months.ConclusionThe application of i-PRF after a subgingival debridement using glycine air-polishing shows significant improvement of clinical parameters and a bone level stability for at least six months. However, if we consider that no bleeding on probing is needed to control the disease, none of the implants were considered successfully treated. Further randomized clinical trials are needed to evaluate the benefits of i-PRF as an adjuvant to the treatment of peri-implantitis.